ANALISIS PERBEDAAN KINERJA KEUANGAN BANK SYARIAH DENGAN MENGGUNAKAN METODE EVA : Studi Kasus Pada PT. Bank Muamalat Tbk. Dan PT. Bank BRI Syariah Tbk. Periode 2015 – 2018. - Miftakhul Huda; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACT               This study intends to analyze the achievement of Islamic banking financial differences using the EVA method at Bank Muamalat and Bank BRI Syariah period of 2015-2018. The research subjects in this study were Bank Muamalat and Bank BRI Syariah the period 2015 - 2018. This research without using hypothesis testing because this research is classified as evaluation research. The researcher used the documentation research method in the form of a Bank Publication Financial Report issued by Bank Muamalat and Bank BRI Syariah 2015 - 2018 period. Financial statements are analyzed for each bank's financial performance using the EVA method to determine the differences in the financial performance of. Bank Muamalat and Bank BRI Syariah. the period 2015 - 2018. Analysis of the data in this study is a qualitative description by processing data into a graph then compared through a description approach, from the results of the calculation of EVA Bank Muamalat and Bank BRI Syariah the period 2015 - 2018. From the analysis of the data obtained the results of the study show that there are significant differences between the financial performance of pure Islamic banks and mixed Islamic banks using the EVA method.Keywords : financial performance, Islamic banks, and EVA methods.